Equity Links and Information Acquisition in Biotechnology Alliances - Darren Filson; Rosa Morales (Claremont McKenna College, Department of Economics, 2001)
We use a simple model of collaborative innovation to structure an empirical analysis of minority equity links in biotechnology alliances between clients and R&D firms. In the model, an equity link is an investment in information acquisition: it improves the ability of the client to learn about the R&D firm's ability and the alliance project's quality. The model generates several testable hypotheses about how the R&D firm's project characteristics and previous alliances affect the use of equity links in new alliances. We test the hypotheses using a large data set of biotechnology alliances and find empirical support.
Keywords: L14; L22; O32; 330; alliance; collaboration; integration; joint venture; technological change